A selective COX-2 inhibitor suppresses chronic pancreatitis in an animal model (WBN/Kob rats): significant reduction of macrophage infiltration and fibrosis. Issue 8 (1st December 2005) - Reding, T; Bimmler, D; Perren, A; Sun, L-K; Fortunato, F; Storni, F; Graf, R
Abstract : Introduction: Therapeutic strategies to treat chronic pancreatitis (CP) are very limited. Other chronic inflammatory diseases can be successfully suppressed by selective cyclooxygenase 2 (COX-2) inhibitors. As COX-2 is elevated in CP, we attempted to inhibit COX-2 activity in an animal model of CP (WBN/Kob rat). We then analysed the effect of COX-2 inhibition on macrophages, important mediators of chronic inflammation. Methods: Male WBN/Kob rats were continuously fed the COX-2 inhibitor rofecoxib, starting at the age of seven weeks. Animals were sacrificed 2, 5, 9, 17, 29, 41, and 47 weeks later. In some animals, treatment was discontinued after 17 weeks, and animals were observed for another 24 weeks. Results: Compared with the spontaneous development of inflammatory injury and fibrosis in WBN/Kob control rats, animals treated with rofecoxib exhibited a significant reduction and delay (p<0.0001) in inflammation. Collagen and transforming growth factor β synthesis were significantly reduced. Similarly, prostaglandin E2 levels were markedly lower, indicating strong inhibition of COX-2 activity (p<0.003). If treatment was discontinued at 24 weeks of age, all parameters of inflammation strongly increased comparable with that in untreated rats. The correlation of initial infiltration with subsequent fibrosis led us to determine the effect of rofecoxib on macrophage migration. In chemotaxis experiments, macrophages became insensitive to the chemoattractant fMLP in the presence of rofecoxib. Conclusion: In the WBN/Kob rat, chronic inflammatory changes and subsequent fibrosis can be inhibited by rofecoxib. Initial events include infiltration of macrophages. Cell culture experiments indicate that migration of macrophages is COX-2 dependent.